Cognition, culture and utility: Plant classification by Paraguayan immigrant farmers in Misiones, Argentina - Kujawska, Monika (2017)
Background: This study was conducted in three rural communities of small farmers of Paraguayan origin living in the province of Misiones, Argentina. These Criollos (Mestizos) hail chiefly from departments located in the east of Paraguay, where the climate and flora have similar characteristics as those in Misiones. These ecological features contribute to the continuation and maintenance of knowledge and practices related to the use of plants. Methods: Fieldwork was conducted between September 2014 and August 2015. Forty five informants from three rural localities situated along the Parana River participated in an ethno-classification task. For the classification event, photographs of 30 medicinal and edible plants were chosen, specifically those yielding the highest frequency of mention among the members of that community (based on data obtained in the first stage of research in 2014). Variation in local plant classifications was examined and compared using principal component analysis and cluster analysis. Results: We found that people classify plants according to application or use (primarily medicinal, to a lesser extent as edible). Morphology is rarely taken into account, even for very similar and closely-related species such as varieties of palms. In light of our findings, we highlight a dominant functionality model at work in the process of plant cognition and classification among farmers of Paraguayan origin. Salient cultural beliefs and practices associated with rural Paraguayan plant-based medicine are described. Additionally, the manner by which residents’ concepts of plants articulate with local folk epistemology is discussed. Conclusions: Culturally constructed use patterns ultimately override morphological variables in rural Paraguayans’ ethnobotanical classification.